2020
DOI: 10.17220/ijpes.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

An Organizational Factor Predicting School Effectiveness: School Climate

Abstract: According to the findings, school climate predicts school effectiveness. The findings were discussed with the results of other researches in the literature and suggestions were made to the administrators and teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
6
0
8
Order By: Relevance
“…The results of research by Davis et al In 2015 show that school climate is an important factor related to student achievement in New York (6). Ozgenel's research results in 2020, show that a positive school climate has an impact on the performance of administrators, educ ators and employees in schools which leads to increased student achievement in Turkey (26). The results of research by Sanders et al in 2018, stated that a positive school climate also affects the academic achievement of students with disabilities in the United States (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of research by Davis et al In 2015 show that school climate is an important factor related to student achievement in New York (6). Ozgenel's research results in 2020, show that a positive school climate has an impact on the performance of administrators, educ ators and employees in schools which leads to increased student achievement in Turkey (26). The results of research by Sanders et al in 2018, stated that a positive school climate also affects the academic achievement of students with disabilities in the United States (27).…”
Section: Resultsmentioning
confidence: 99%
“…From several studies on positive school climate, it can be concluded that in general a positive school climate can affect student achievement. In addition, a positive school climate can also influence students' emotions, behavior, reduce the harmful effects of low SES, increase the developmental stresses of early adolescence and increase student contributions to school activities (23) (24) (10) (25) (6) (26). However, some research results reveal that school climate and academic achievement have a significant relationship.…”
Section: Resultsmentioning
confidence: 99%
“…For example, principals focus on measuring the aspects of school bureaucracy as an input to measuring effectiveness, such as maintaining order and adhering to instructions and laws, engaging teachers to build a school culture for continuous improvement, and controlling different school activities to maintain focus on educational tasks and to ensure that teachers work and fulfill their responsibilities in accordance with the school's educational goals (Özgenel, 2020(Özgenel, , Gray,2016. As for the teachers, they focus on the teaching methods, processes and activities that they practice (European Commission, 2019), On the other hand, students, parents and the local community focus on school productivity by measuring students 'achievement, their academic level and the value system they carry (OECD, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Okul etkililiği kavramının tanımlanması ve ilişkiler ağının belirlenmesi açısından geçen yaklaşık elli yıldan beri eğitim araştırmacıları açısından konu merkezi ve başat rolünü kaybetmemiş ve birçok kuramsal (Balcı, 2002;Marzano, 2012;Sergiovanni, 2006; çalışma yapılmıştır. Bunun yanısıra okul etkililiği kavramının etkilediği ya da etkilendiği faktörleri belirlemek için pozitif psikolojik sermaye (Çiftçi, 2019), liderlik ve liderlik stilleri (Baştoklu, 2015;Ermeydan, 2019;Namlı, 2017), örgütsel iklim (Özgenel, 2020;Şenel ve Buluç, 2015), akademik başarı (Korkmaz vd., 2014;Oldaç, 2016), örgütsel öğrenme (Akgül, 2014;Alanoğlu, 2014) gibi birçok ampirik araştırmanın yapıldığı görülmektedir.…”
Section: Introductionunclassified